Bridging the Narrative Gap: The Ghost Narrator in Marlon James’s A Brief History of Seven Killings (2014) - Tomczak, Anna Maria (Hungarian Journal of English and American Studies, 2020)
The essay reads Marlon James’s A Brief History of Seven Killings (2014) in the context of Walter D. Mignolo’s discussion on “border thinking” and “border gnosis” in Local Histories/Global Designs: Coloniality, Subaltern Knowledges and Border Thinking (2000). Through introducing the narrative voice of Sir Arthur Jennings Marlon James creates a link between past and present, between Caribbean and European tradition of cultures of orality and literacy, and between pre- and post-colonial times, critically engaging in the erasure of thresholds of epistemological location. Specific attention is paid to Sir Arthur’s role as a “duppy” (a ghost or spirit in the religious practice of Obeah) and as a “griot” (an African/Caribbean bard and story-teller) whose function is to narrate and document local histories and guard verbal art traditions of the community. (AMT)